Right to be forgotten: European instruments to protect the rights of cancer survivors - Napoletano, Gabriele; De Paola, Lina; Circosta, Francesco; Montanari Vergallo, Gianluca (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Cancer survivors, even many years after their illness, are often excluded or discriminated against in accessing funding, insurance contracts, child adoptions, and other aspects of social life. Methods: The authors conducted a search on the PubMed database using the keywords "cancer survivor" and "right to be forgotten," also drawing upon national and international legal, judicial and regulatory sources. The aim of the study is to analyze the scope of the phenomenon and identify suitable tools to counteract this discrimination. Results: Several European countries, including France, Belgium, Luxembourg, the Netherlands, Portugal, Romania, and Italy, have implemented laws specifically addressing the "right to be forgotten" for cancer survivors. This legal recognition stems from advancements in scientific research that have reduced cancer mortality and morbidity. These laws grant individuals the right not to disclose their past illness after a certain period of being disease-free, even during financial procedures or insurance applications. The European Union has encouraged other states to enact similar legislation to ensure uniform protection for cancer survivors. Conclusions: The regulations introduced by some European countries currently provide essential assistance to former patients to facilitate access to insurance and financial products otherwise unavailable. However, relying on the expectation that scientific research will produce increasingly strong evidence in this field, it is possible to envisage a future in which, regardless of regulations, the market itself will find these categories of people desirable to expand its sales channels.